Maturation is prolonged and variable in female chimpanzees. Issue 114 (January 2018) - Walker, Kara K.; Walker, Christopher S.; Goodall, Jane; Pusey, Anne E.
Abstract: Chimpanzees are important referential models for the study of life history in hominin evolution. Age at sexual maturity and first reproduction are key life history milestones that mark the diversion of energy from growth to reproduction and are essential in comparing life history trajectories between chimpanzees and humans. Yet, accurate information on ages at these milestones in wild chimpanzees is difficult to obtain because most females transfer before breeding. Precise age at first birth is only known from a relatively small number of non-dispersing individuals. Moreover, due to small sample sizes, the degree to which age at maturation milestones varies is unknown. Here we report maturation milestones and explore sources of variance for 36 wild female chimpanzees of known age, including eight dispersing females born in Gombe National Park, Tanzania. Using Kaplan-Meier survival analysis, including censored intervals, we find an average age of 11.5 years (range 8.5–13.9) at sexual maturity and 14.9 years (range 11.1–22.1) at first birth. These values exceed previously published averages for wild chimpanzees by one or more years. Even in this larger sample, age at first birth is likely underestimated due to the disproportionate number of non-dispersing females, which, on average, give birth two years earlier than dispersing females. Model selection using Cox Proportional Hazards models shows that age at sexual maturity is delayed in females orphaned before age eight years and those born to low-ranking mothers. Age at first birth is most delayed in dispersing females and those orphaned before age eight years. These data provide improved estimates of maturation milestones in a population of wild female chimpanzees and indicate the importance of maternal factors in development.